Urgency of Legal Aspects in Management of Featured Products as an Effort to Empower Communities in the Circle Campus Area - Martitah, Martitah; Sulistianingsih, Dewi; Arifin, Saru (Indonesian Journal of Advocacy and Legal Services, 2019)
The strategy of strengthening a competitive domestic economy supported by agricultural development is a strategy that is close to the countryside. Pakintelan is a village located in Gunungpati District, Semarang City. The vast area of the Pakintelan Village is a capital or asset for the people of Pakintelan to make a living because most of the people of Pakintelan are farmers and traders. The purpose of this program is to identify the legal aspects in the management and marketing of superior products in Pakintelan Gunungpati Semarang. The method used in this program in addition to socialization, also carried out observation and documentation of existing resources. This paper confirms that strengthening the legal aspects in the management and marketing of superior products in Indonesia, especially in Pakintelan, Semarang, Central Java, is becoming very important in the midst of globalization and industrial growth. Strengthening these legal aspects must also be supported and carried out by various elements of society including the sword community and the community around the Semarang State University campus which is one of the target markets in the Pakintelan community's small business.